Signalling Cascades in Melanoma: Understanding the Potential of Phytochemicals as Inhibitors - Indira Chakraborty; Aniruddha Banerji (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
Melanoma has the highest mortality rate among all the dermatological cancers and shows poor prognosis if metastasis and secondary tumour formation occur. Deregulation of cellular signalling pathways like the phosphatidylinositol 3’ kinase (PI3K) / Akt pathway, extracellular signal regulated kinase (ERK) pathway and the nuclear factor kappa beta (NF-\(κ\)\(β\)) pathway play important roles in development, progression and metastasis of melanomas. This article focuses on how such signalling pathways could be possible therapeutic targets for treatment of melanomas by the use of natural phytochemical compounds. Studies indicate that many natural phytochemical compounds such as all-trans retinoic acid, kaempferol, curcumin, betulinic acid, parthenolide and epigallocatechin gallate appear to have good potential to act as signalling pathway inhibitors for melanoma therapy. As many of these phytochemicals and their plant sources are already a part of human diet, using these natural compounds could help in reducing side effects and lowering treatment costs. Thus, targeting cellular signalling pathways with natural phytochemical compounds could lead to development of effective clinical strategies for melanoma treatment.